Survival in Elderly Ovarian Cancer Remains Challenging in the Nordic Countries - Hemminki, Kari; Zitricky, Frantisek; Försti, Asta; Hemminki, Akseli (Cancers, 2024)
BACKGROUND: Despite treatment having improved through intensive surgical procedures and chemotherapy-and more recently, targeted therapies-ovarian cancer is the most fatal female cancer. As such, we wanted to analyze age-specific survival trends for ovarian cancer in Denmark, Finland, Norway and Sweden over the past 50 years, with a special aim of comparing survival development between the age groups. METHODS: We modelled survival data from the NORDCAN database for 1-, 5- and conditional 5/1-year relative (between years 1 and 5) survival for ovarian cancer from 1972 to 2021. RESULTS: Young patients had a 70% 5-year survival while the survival was only 30% for the oldest patients. Conditional survival showed that survival between years 1 and 5 did not improve for patients older than 60 years throughout the 50-year period, during which time the gaps between the youngest and the oldest patients widened. CONCLUSIONS: Improvement in 1-year survival was so large that it masked the modest development between years 1 and 5, resulting in a widening age disparity in 5-year survival. The current treatment practices, which appear increasingly effective for younger patients, have not helped remedy the large age differences in ovarian cancer survival. Early detection methods and therapeutic innovations are urgently needed, and aged patients need a special focus.
Keywords: carboplatin cancer control; prognosis; treatment; relative survival